1939
DOI: 10.1017/s0022172400059556
|View full text |Cite
|
Sign up to set email alerts
|

Cross Immunity Experiments in Monkeys Between Variola, Alastrim and Vaccinia

Abstract: PART I. VARIOLA AND VACCINIA IN spite of the voluminous literature, much of it of a polemical rather than scientific nature, on the immunity relationships between variola and vaccinia, comparatively little work has been carried out on experimental animals, and the results of different workers are not altogether concordant. Even in the important article by Blaxall (1930) in the System of Bacteriology only a few lines were devoted to a discussion of the existing experimental evidence, and also in the more recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1940
1940
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…In other studies with variola and alastrim viruses (40), it was also found that immunity was not fully reciprocal, but that the degree of protection induced by alastrim was greater than that by variola. This finding was of considerable interest, because the variola strain used was the most virulent for monkeys isolated in the Sudan, and the alastrim was incapable of producing more than a local reaction.…”
Section: E Cross-immunity Relationshipsmentioning
confidence: 81%
See 3 more Smart Citations
“…In other studies with variola and alastrim viruses (40), it was also found that immunity was not fully reciprocal, but that the degree of protection induced by alastrim was greater than that by variola. This finding was of considerable interest, because the variola strain used was the most virulent for monkeys isolated in the Sudan, and the alastrim was incapable of producing more than a local reaction.…”
Section: E Cross-immunity Relationshipsmentioning
confidence: 81%
“…In general, laboratory techniques for distinguishing between the viruses of variola and alastrim have failed to reveal constant differences with regard to the histology of skin lesions (21,28), the lesions produced on the chorioallantoic membrane of embryonated eggs (28), cross-immunity experiments in monkeys (40), serum-neutralization, complement-fixation, and hemagglutination-inhibition tests (25,27,47), by the double-diffusion precipitation technique (35), and the use of laboratory animals (22). Within recent years, however, the findings from studies of the behavior of smallpox and alastrim viruses in embryonated eggs offer a means of differentiating them.…”
Section: Pathogenicity and Virulence Of Poxvirus Strainsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a rule, the disease is generalized with the development of a rash of varying severity in different species of primates. In almost all respects it resembles naturally occurring variola in man (25,65) and experimental variola in monkeys (14,35,37,42,47,59,76). The incubation period of the disease in experimentally infected animals has varied from 7 to 14 days in cynomolgus and rhesus monkeys, and in baboons (40,73,75).…”
Section: Clinical Manifestationsmentioning
confidence: 92%